Serological status for Toxoplasma gondii and cytomegalovirus in pregnant women - Ayad Almakki; Zuhair Al Shaheen; Alaa Alali (Romanian Journal of Infectious Diseases)
Background and objective. Toxoplasma gondii and CMV cause congenital defects in TORCH (Toxoplasmosis, Rubella virus, cytomegalovirus, and Herpes simplex virus) infections. The primary objective of the study was to estimate the seroprevalence of Toxoplasma gondii (TOXO) and cytomegalovirus (CMV) infections among pregnant women in Al Qurnah, Iraq, and identify the presence of specific Immunoglobulin M (IgM) antibodies indicating recent infections. Material and method. The study tested 1000 healthy pregnant women using VIDAS® TOXO and CMV IgM kits. Results. The findings revealed a significant seroprevalence, with 37.2% of samples positive for Toxoplasma IgM, 22.8% for CMV IgM, and 9.6% for mixed infections. The highest rate of abortions occurred in the first trimester, with a significant increase in abortion parameters among pregnant women infected with T. gondii and CMV. Our study comprised 372 pregnant women with Toxoplasma infection; 286 (76.9%) were rural and 86 (23.1%) urban. Our analysis identified CMV in 228 pregnant women, 159 rural (69.7%), and 69 urban (30.3%). Conclusion. The study suggests a higher prevalence of Toxoplasma IgM compared to CMV IgM infections in the region, emphasizing the importance of early detection and prevention, especially during the first trimester. The results also highlight the need for routine antenatal screening and educational measures to reduce the impact of these infections on pregnancy outcomes.